2004
DOI: 10.1111/j.1365-2869.2004.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cognitive arousal on sleep latency, somatic and cortical arousal following partial sleep deprivation

Abstract: SUMMAR Y Emerging research has shown that sleepiness, defined as the tendency to fall asleep, is not only determined by sleep pressure and time of day, but also by physiological and cognitive arousal. In this study we evaluated (i) the impact of experimentally induced cognitive arousal on electroencephalogram (EEG) defined sleep latency, and subjective, somatic and cortical arousal, and (ii) whether experimentally induced cognitive arousal enhances performance on a driving simulator test. Twelve healthy sleepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 44 publications
(59 reference statements)
1
17
0
Order By: Relevance
“…With regard to this issue, two studies already showed that a quasi-desensitization placebo was associated with improved subjective sleep only when the participants were told that it was beneficial (Steinmark and Borkovec 1974;Carr-Kaffashan and Woolfolk 1979). However, in the present study, the suggestion of the pills' efficacy, although present, was not emphasized, since a stronger suggestion may have induced cognitive arousal resulting in significant increases in objective sleep latency (e.g., De Valck et al 2004). In fact, sleep latency did not change as compared to the BSL night.…”
Section: Methodological Issuesmentioning
confidence: 65%
“…With regard to this issue, two studies already showed that a quasi-desensitization placebo was associated with improved subjective sleep only when the participants were told that it was beneficial (Steinmark and Borkovec 1974;Carr-Kaffashan and Woolfolk 1979). However, in the present study, the suggestion of the pills' efficacy, although present, was not emphasized, since a stronger suggestion may have induced cognitive arousal resulting in significant increases in objective sleep latency (e.g., De Valck et al 2004). In fact, sleep latency did not change as compared to the BSL night.…”
Section: Methodological Issuesmentioning
confidence: 65%
“…Kronholm et al, 1995;Pressman and Fry, 1989). Furthermore, several experimental studies Arand, 1998, 2005a;De Valck et al, 2004;Gross and Borkovec, 1982;Haynes et al, 1981;Wuyts et al, 2012) have shown that transient increases in physiological or cognitive arousal before going to sleep result in a prolonged latency of sleep onset, which indicates reduced sleepiness. A potential limitation of these studies is the use of a single or few indicators of arousal, most commonly heart rate, since arousal is a multidimensional construct and the congruence between different measures of arousal is either small or insignificant (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have already shown its relationship with (optimal) cognitive performance (Vernon et al 2003;Gruzelier 2001, 2004;Sterman 1996;Hanslmayer et al 2005) as well as sleep improvement and sleep spindle density (Sterman et al 1970;Hauri 1981;Hauri et al 1982;Berner et al 2006). Thirdly, high beta power (20-30 Hz), which appears to be linked with cognitive processes (Basar-Eroglu et al 1996;Jefferys et al 1996;Makeig and Jung 1996) and arousal (De Valck et al 2004), and is increased in patients experiencing insomnia during the SOP (Lamarche and Ogilvie 1997) and sleep (Perlis et al 2001), was inhibited. The main goal was not to actively decrease the amount of high beta power, but stabilize the reactivity on arousal and stress reflected by the possible instability of this EEG frequency band.…”
Section: Introductionmentioning
confidence: 95%
“…Taken in to account that patients with insomnia report high stress levels during daytime functioning, and thus more cognitive arousal at bedtime, the increased high beta power during SO and sleep might also be related to the stress and anxiety. De Valck et al (2004) showed that experimentally induced cognitive arousal in healthy sleepers resulted in increased subjective arousal, augmented cortical arousal reflected by high beta EEG power, as well as increased sleep latency.…”
Section: Introductionmentioning
confidence: 99%